Tendenser inom interpretationer av Alexander Skrjabins pianosonat nr. 10 : en jämförande pianistisk analys - Lettberg, Maria (Sibelius-Akatemia, 2008)
The aim of this work is to examine the most important aspects in the interpretation of Alexander Scriabin's (1872–1915) Piano Sonata No. 10, Op. 70. The beginning of this analysis focuses on the reconstruction of the appearance of Scriabin as pianist, his technical and aesthetic principles. This reconstruction is produced by comparing printed chronicles such as memoirs of Scriabin's contemporaries, the composer's own letters and diaries, and the academic research literature with regard to interpretations and studies of Scriabin's audio records, recorded by "Phonola" and "Welte-Mignon". Furthermore, the audio records of the interpretations of the Scriabin's 10th sonata by the most important pianists of the twentieth century have been analysed. The interpretations of Heinrich Neuhaus, Vladimir Sofronitskij, Vladimir Horowitz, Vladimir Ashkenazy, Roberto Szidon, John Ogdon, Igor Zhukov, Håkan Austbø, Ruth Laredo, Boris Berman, Mikhail Pletnev, Mark-André Hamelin, Arkadi Volodos are studied and described by the method of comparative pianistic analysis. The conclusion reveals characteristic features of the development of the tendencies which were observed in the interpretations of these pianists. These aspects of interpretation correspond to the basic features of Scriabin as pianist. The result of the study is the clarification of the most important aspects in the performance of Scriabin's music.

I denna uppsats studeras de viktigaste aspekterna för interpretation av pianosonat nr 10 opus 70 av Alexander Skrjabin (1872–1915). Den inledande delen är ägnad åt rekonstruktion av Skrjabins gestalt som pianist och klarläggande av hans tekniska och estetiska principer. Arbetet utförs genom en komparativ studie av tryckta utgåvor, som krönikor, memoarer av Skrjabins samtida, brev, tonsättarens egna dagböcker samt vetenskaplig forskningslitteratur, som rör dechiffrering och undersökning av Skrjabins egna inspelningar, gjorda på apparaterna "Phonola" och "Welte-Mignon". Vidare analyseras interpretationer av Skrjabins sonat nr 10, utförda av framstående pianister på 1900-talet och dokumenterade på fonogram. Interpretationerna av Heinrich Neuhaus, Vladimir Sofronitskij, Vladimir Horowitz, Vladimir Ashkenazy, Roberto Szidon, John Ogdon, Igor Zhukov, Håkan Austbø, Ruth Laredo, Boris Berman, Mikhail Pletnev, Mark-André Hamelin och Arkadi Volodos studeras och beskrivs med hjälp av jämförande pianistisk interpretationsanalys. Slutligen undersöks utvecklingen av de tendenser som har iakttagits i interpretationer av aktuella pianister. De betecknande aspekterna i dessa interpretationer refereras sedan till typiska särdrag hos Skrjabin som pianist. Undersökningens resultat innefattar ett klarläggande av de viktigaste aspekterna för utförande av Skrjabins musik.
Keywords: Skrjabin, Aleksandr. Sonaatit, piano, nro 10, op70.; musiikkianalyysi; sonaatit; piano; DocMus